Gender Patterns in Labor Allocation to Avocado Production: Evidence from Kenya - Edna G. Johnny; Jane Kabubo-Mariara; Richard Mulwa; George M. Ruigu (European Scientific Journal, ESJ, 2019)
Farmers face gender differentiated unique social and economic circumstances which may in part determine their time allocation behavior. Using primary survey data from Murang’a County, Kenya, this study employs the double hurdle and Tobit models to investigate gendered patterns of labor allocation in avocado production under contract and non-contract scenarios, non-farm activities as well as the intensity of time use. Results show that while avocado commercialization through contract farming has to some extent altered traditional gender roles in farming, there is still limited participation of women in avocado marketing under contract farming. Hence, interventions aimed at enhancing smallholder avocado production should incorporate mechanisms that will enable women participate at all levels of the avocado value chain.